A oferta da dança sênior na atenção básica do município de Pirassununga/SP : “caminhos” favoráveis à sua implantação - Nascimento, Simone Mattos do (Universidade Federal de São Carlos, 2016)
INTRODUCTION: Senior Dance can be one of the Action Fitness / Body Practices to be integrated as a relevant therapeutic project within the guidelines of primary care and performed at USF, UBS and NASF. OBJECTIVE: This qualitative, exploratory and descriptive research has the purpose to identify factors conductive to offer Senior Dance in primary care in the city of Pirassununga/ SP, as regards its implementation. MATERIALS AND METHODS: The study included health managers, professionals from high level, the Community Agents of Health (CHA) and the elderly users of USF (n=14). All signed the Term of Free and Clear (IC) research and images. 30% of the six selected USFs, where the supply of Dance Senior possible, all answered the Senior Dance Offer questionnaire at baseline and after three months of activity. Additionally the elderly answered the SF-36 lifequality questionnaires at baseline and after three months of activity and were undergo multidisciplinary assessment geriatric and gerontology Dance Senior. The project was approved by the Ethics Committee of the Platform Brazil's Federal University of São Carlos, opinion No. 895,345. In the data tract was used content analysis. RESULTS AND DISCUSSION: It was possible to perform a characterization of the clinical data of elderly participants of the Senior Dance by analysis of geriatric assessment and multidisciplinary gerontology Dance Senior. This evaluation was given emphasis to the clinical diagnosis and the result of evaluating the quality of life; anthropometric measurements; mobility through balance and gait; and up and go to the elderly. In the approach to dance Senior offer questionnaires, from the perception of health managers, the top health professionals level of CHWs and elderly users who participated in the dance emerged five speeches: Speech 1: "Knowledge of the Dance Senior"; Speech 2: "The improvement and maintenance of health and the elderly quality of life"; Speech 3: "The level of satisfaction with the Senior Dance"; Speech 4: "Access to health services in AB Attention basically" and Speech 5: "The ways favorable to the implementation of the Senior Dance USFs in view of health managers, the top-level health professionals and Community Health Workers (CHWs) and elderly. " CONCLUSION: The ways that favored the offer of dance in Senior USFs were the grip and adhesion of the elderly participants the new intervention; the satisfaction of the participants with regard to Senior Dance; maintenance quality of life of elderly participants; a new lowcost intervention. In this context, the Senior Dance presented as viable and applicability in primary care, since both managers and health professionals have felt strengthened by the support matrix conducted by physiotherapist in providing mode.
Keywords: Atenção primária à saúde; Estratégia saúde da família; Idoso; Fisioterapia; Terapia através da dança; CIENCIAS DA SAUDE